2017
DOI: 10.1292/jvms.17-0174
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of quantitative contrast-enhanced ultrasonography for assessing duodenal perfusion in healthy dogs

Abstract: Contrast-enhanced ultrasonography (CEUS) with microbubbles as a contrast agent allows the visualization and quantification of tissue perfusion. The assessment of canine intestinal perfusion by quantitative CEUS may provide valuable information for diagnosing and monitoring chronic intestinal disorders. This study aimed to assess the repeatability (intraday variability) and reproducibility (interday variability) of quantitative duodenal CEUS in healthy dogs. Six healthy beagles underwent CEUS three times within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 34 publications
1
15
2
Order By: Relevance
“…Moreover, heart rate is negatively correlated with time‐to‐peak in the feline kidney and canine duodenum . Mean arterial pressure, on the other hand, is not correlated with any contrast‐enhanced ultrasound parameters in the canine duodenum . Nevertheless, time‐to‐peak in this study had the lowest amount of variability.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Moreover, heart rate is negatively correlated with time‐to‐peak in the feline kidney and canine duodenum . Mean arterial pressure, on the other hand, is not correlated with any contrast‐enhanced ultrasound parameters in the canine duodenum . Nevertheless, time‐to‐peak in this study had the lowest amount of variability.…”
Section: Discussioncontrasting
confidence: 55%
“…One of the limitations of the current study was that blood pressure and heart rate values were not measured during contrast‐enhanced ultrasound examinations, and both of these measures could possibly have contributed to the variation of perfusion parameters . Although not high, interday variability of heart rate and mean arterial pressure of dogs sedated with butorphanol and midazolam is 18.3% and 9.5%, respectively . Furthermore, mean peak enhancement, wash‐in perfusion index and wash‐out rate for the entire kidney decreases in cats with increased systolic blood pressure due to infusion with angiotensin II .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Enhancement intensity was measured by drawing 4 regions of interest (ROIs) as large as possible in the duodenal mucosa at approximately the same depth and without including major vessels or adjacent tissue. Analysis using 4 ROIs was selected because it exhibited the best repeatability compared to other methods . If 4 ROIs could not be drawn because of motion artifacts, 1, 2, or 3 ROIs were drawn instead.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that CEUS allows characterization of intestinal perfusion in healthy dogs . The assessment of perfusion parameters derived from duodenal CEUS in healthy dogs is clinically acceptable because of its repeatability and reproducibility . However, further studies in dogs with intestinal diseases are warranted to investigate the clinical applicability of this technique as a diagnostic modality.…”
Section: Introductionmentioning
confidence: 99%